Financial literacy as a driver of financial inclusion in Kenya and Tanzania - Ashenafi Beyene Fanta; Kingstone Mutsonziwa (Journal of Risk and Financial Management, 2021)
Efforts are being exerted in many developing countries to promote financial inclusion by increasing individuals' access to financial products and services. However, literature suggests that increasing the supply of financial products and services per se may not help in expanding financial inclusion unless concerted efforts are exerted in enhancing financial literacy. This is because financially literate individuals are more likely to appreciate the value of financial services and hence take up financial products. This paper reports the link between financial literacy and inclusion using data from a demand side financial inclusion survey conducted in Kenya and Tanzania in 2016 covering a total of 6029 individuals. Results from our instrumental variable regression analysis confirmed that financial literacy is a strong driver of financial inclusion. This implies that efforts to promote financial inclusion need to be accompanied with financial literacy campaigns in both countries.
Keywords: 330; East Africa; instrumental variable; financial knowledge; financial behaviour